2011
DOI: 10.5187/jast.2011.53.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kaolin (Natural Ligneous Clay) Supplementation on Performance and Egg Quality in Laying Hens

Abstract: Two experiments were conducted to determine the effects of supplementing different levels of kaolin (Exp. 1) and effects of age of layers and levels of kaolin (Exp. 2) on the performance, egg and shell quality parameters of laying hens. In Exp.1, 64 laying hens of 58 wks age were randomly allotted to 4 treatments of 16 hens in each. Dietary treatments were basal diet supplemented with 0.0, 0.2, 0.4 and 0.6% kaolin. In Exp. 2 96 laying hens were divided into 6 groups of 16 hens each in a 2 x 3 factorial arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
5
2
1
Order By: Relevance
“…The percentage of egg laying was not influenced by the inclusion of kaolin (Table 2). These results contrasted with those reported by KIM et al (2011) which showed that using lower kaolin levels in the diets of 58-week-old laying hens (0%-0.6% of the additive), caused an increase in egg yield of 0.2%. The laying rate observed in this experiment related to the average laying advocated by the line management guide (HENDRIX GENETICS, 2016), regardless of the inclusion of kaolin.…”
Section: Resultscontrasting
confidence: 99%
“…The percentage of egg laying was not influenced by the inclusion of kaolin (Table 2). These results contrasted with those reported by KIM et al (2011) which showed that using lower kaolin levels in the diets of 58-week-old laying hens (0%-0.6% of the additive), caused an increase in egg yield of 0.2%. The laying rate observed in this experiment related to the average laying advocated by the line management guide (HENDRIX GENETICS, 2016), regardless of the inclusion of kaolin.…”
Section: Resultscontrasting
confidence: 99%
“…According to Safaeikatouli et al (2012), the inclusion of clays in animal feed reduces the passage rate of digesta, improving digestibility, which causes birds to consume less feed to meet their nutritional requirements. Similar to the present study, Kim et al (2011) also observed lower feed intake after inclusion of clay (kaolin) in the feed of laying hens.…”
Section: Discussionsupporting
confidence: 91%
“…Egg weight, Haugh unit, yolk index, percentage of albumin and shell, and eggshell thickness were kept at good quality regardless of the level of kaolin used (p>0.05). Similar to that observed in this study, Kim et al (2011) also found no significant difference for variables of internal quality and eggshells produced by laying hens fed several levels of clay (kaolin). Homer (1980) reported reduced water content in the excreta through an experiment with laying hens fed diets containing 2.5 and 5% bentonite compared to a control diet without clay.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations